Simple Phantom for Insertion of Intrauterine Contraceptive Device (IUD) Innovation: Learning Methods during The Covid-19 Pandemic - Ayu Endang Purwati; Sri Utami Asmarani; Sandriani Sandriani (Genius Journal, 2024)
Objective: The purpose of this research is to make and create a simple IUD insertion phantom that can be used by lecturers and students in the teaching and learning process, making it easier for students to do the practicum learning process at home. Method: The method used in this development is the research and development (R&D) method. Result: The feasibility results of the validation of the phantom display by experts were obtained as much as 93%; the validation of the phantom function was 95%; the field trial resulted in a student response of 89.5% related to the phantom display and 99% of the phantom function. Conclusion: A simple phantom of intrauterine contraceptive device insertion innovation of learning method during the COVID-19 pandemic is created and can be used.